Metamorphosis through conscious living : a transpersonal psychology perspective - McMullin, Lindy; Hess, Regina U.; Boucouvalas, Marcie, 1947- (Cambridge Scholars Publishing, 2017)
Metamorphosis, the theme of this book, derives from the Ancient Greek language and refers to a transformative process that often includes disintegration and reintegration, on the route to conscious living with self, community and the world. This collection proposes that engagement with the sacred is what makes research and practice transpersonal, the sacred 'other' that lives both within and beyond us as individuals and unique cultures. The transpersonal approach is distinctive in that it regards the potential metamorphosis of all those involved in research and professional practice a core val.